A new species of Passandra Dalman (Coleoptera: Passandridae) from the Philippines and Borneo - Bukejs, Andris (Zootaxa, 2019)
Passandra barsevskisi sp. nov. (Coleoptera: Passandridae) is described and illustrated from Borneo and the Philippines. The new species can be distinguished from all known species of Passandra by the following combination of features: head, pronotum and elytra black; antennomeres 3–10 with narrow groove ventrally, male antennae robust with antennomeres 4–10 swollen; admedian grooves of head deep, long, almost straight, slightly diverging anteriorly; median process of head well developed and reaching occipital groove; pronotal disc with two deep and long admedian grooves; pronotal sublateral lines entire, widely separated anteriorly; submarginal basal groove deeply and narrowly emarginate medially in male, notched in female; each elytron with lines I and VI complete, lines II and V incomplete; and median lobe of aedeagus with triangular apical portion and rounded apex.